2019
DOI: 10.1038/s41598-019-45310-z
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen heterocycles form peptide nucleic acid precursors in complex prebiotic mixtures

Abstract: The ability to store information is believed to have been crucial for the origin and evolution of life; however, little is known about the genetic polymers relevant to abiogenesis. Nitrogen heterocycles (N-heterocycles) are plausible components of such polymers as they may have been readily available on early Earth and are the means by which the extant genetic macromolecules RNA and DNA store information. Here, we report the reactivity of numerous N-heterocycles in highly complex mixtures, which were generated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 82 publications
0
22
0
Order By: Relevance
“…Although we explored considerable molecular diversity here, there are numerous structural modifications of the compounds in this study that should be similarly polymerizable and may have additional interesting prebiotically relevant properties. The elongation mechanisms discussed here have already been shown to be useful for oligomerizing nucleoside cyclic phosphates 40,41 , and should be applicable to nucleoside analogues as well, of which it seems there could have been a very large prebiotic variety 46,[77][78][79][80] .…”
Section: Prebiotic Relevance the Development Of Autocatalytic And Sementioning
confidence: 88%
“…Although we explored considerable molecular diversity here, there are numerous structural modifications of the compounds in this study that should be similarly polymerizable and may have additional interesting prebiotically relevant properties. The elongation mechanisms discussed here have already been shown to be useful for oligomerizing nucleoside cyclic phosphates 40,41 , and should be applicable to nucleoside analogues as well, of which it seems there could have been a very large prebiotic variety 46,[77][78][79][80] .…”
Section: Prebiotic Relevance the Development Of Autocatalytic And Sementioning
confidence: 88%
“…This synthetic path was also proposed by Miller for the formation of Îł-functionalized amino acids such as methionine . A prebiotic precedent for the formation of β-nucleobase-functionalized aldehydes was also recently demonstrated by Rodriguez et al, who found that Miller–Urey-type electrolysis reactions in a reducing atmosphere above aqueous solutions containing nucleobases produced 1,4 addition products of nucleobases (canonical or noncanonical) with Michael acceptors, including acrolein …”
Section: Resultsmentioning
confidence: 64%
“…It also follows traditional Watson-Crick base pairing rules [42]. Notably, recent work shows N-heterocycles synthesized via electric discharge in neutral and reducing atmospheres form carbonyl side chains, lending support to the possible use of PNA in prebiotic systems [44].PNA does not have a charged backbone, a feature that aids in solubility and discourages folding, however, it is able to grow longer than other uncharged RNA analogs [45]. Interestingly, PNA-based life could to some extent be distinguished based on a C:N ratio, which has limited variability in peptides, but significant grayness would persist due to known abiotic synthesis pathways of its components.…”
Section: Information Storage Systemsmentioning
confidence: 73%